Analysis of Dipylidium caninum tapeworms from dogs and cats, or their respective fleas - Labuschagne Michel; Beugnet Frédéric; Rehbein Steffen; Guillot Jacques; Fourie Josephus; Crafford Dionne (Parasite, 2018)
A 28S rDNA PCR detection assay was previously developed to identify Dipylidium caninum DNA inside single fleas collected from both cats and dogs. Sequence analysis of the 28S rDNA fragment indicated two genetically distinct variations of the target region. The two genotypes, so-called “D. caninum canine genotype” and “D. caninum feline genotype”, based on host origin, are further investigated and described in this paper. Restriction fragment length polymorphism (RFLP) analysis and hydrolysis probe-based genotyping assays were developed and validated for genotyping D. caninum DNA. The complete mitochondrial (mt) genome of the “feline genotype” was sequenced and compared to the D. caninum mt genome available in GenBank. The molecular characterization of D. caninum isolates collected from infected fleas, and also proglottids collected from dogs and cats, confirmed the existence of two distinct genotypes. These genotypes are related to host origin (dogs or cats), irrespective of their geographical origin, and they present a biological adaptation to their respective host, as confirmed by the comparison of biological development and host preference in another study. The genetic differences (Part 1, present paper) and biological observations (Part 2, in this journal) enabled us to suggest the existence of two distinct species within D. caninum, which will have to be clarified.